English

Without using truth table, show that (p ∨ q) → r ≡ (p → r) ∧ (q → r) - Mathematics and Statistics

Advertisements
Advertisements

Question

Without using truth table, show that

(p ∨ q) → r ≡ (p → r) ∧ (q → r)

Sum

Solution

L.H.S.

≡ (p ∨ q) → r

≡ ~ (p ∨ q) ∨ r          ....[p → q → ~ p ∨ q]

≡ (~ p ∧ ~ q) ∨ r       ....[De Morgan’s law] 

≡ (~ p ∨ r) ∧ (~ q ∨ r)       .....[Distributive law]

≡ (p → r) ∧ (q → r)             .....[p → q → ~ p ∨ q]

= R.H.S.

shaalaa.com
  Is there an error in this question or solution?
Chapter 1: Mathematical Logic - Exercise 1.9 [Page 22]

APPEARS IN

RELATED QUESTIONS

The negation of p ∧ (q → r) is ______________.


Without using the truth table show that P ↔ q ≡ (p ∧ q) ∨ (~ p ∧ ~ q)


Using the rules of negation, write the negatlon of the following: 

(a) p ∧ (q → r)

(b)  ~P ∨ ~q


Write the Truth Value of the Negation of the Following Statement :

The Sun sets in the East. 


Write the truth value of the negation of the following statement : 

cos2 θ + sin2 θ = 1, for all θ ∈ R 


Rewrite the following statement without using if ...... then.

If a man is a judge then he is honest.


Rewrite the following statement without using if ...... then.

It 2 is a rational number then `sqrt2` is irrational number.


Without using truth table prove that:

(p ∧ q) ∨ (∼ p ∧ q) ∨ (p ∧ ∼ q) ≡ p ∨ q


Without using truth table prove that:

∼ [(p ∨ ∼ q) → (p ∧ ∼ q)] ≡ (p ∨ ∼ q) ∧ (∼ p ∨ q)


Using the rules in logic, write the negation of the following:

(p ∨ q) ∧ (q ∨ ∼r)


Using the rules in logic, write the negation of the following:

p ∧ (q ∨ r)


Using the rules in logic, write the negation of the following:

(p → q) ∧ r


Using the rules in logic, write the negation of the following:

(∼p ∧ q) ∨ (p ∧ ∼q)


Let p ∧ (q ∨ r) ≡ (p ∧ q) ∨ (p ∧ r). Then, this law is known as ______.


Without using truth table, show that

~ [(p ∧ q) → ~ q] ≡ p ∧ q


Using the algebra of statement, prove that

[p ∧ (q ∨ r)] ∨ [~ r ∧ ~ q ∧ p] ≡ p


Using the algebra of statement, prove that

(p ∨ q) ∧ (~ p ∨ ~ q) ≡ (p ∨ ~ q) ∧ (~ p ∨ q)


For any two statements p and q, the negation of the expression (p ∧ ∼q) ∧ ∼p is ______ 


(p → q) ∨ p is logically equivalent to ______ 


The negation of p → (~p ∨ q) is ______ 


The statement pattern [∼r ∧ (p ∨ q) ∧ (p ∨ q) ∧ (∼p ∧ q)] is equivalent to ______ 


(p ∧ ∼q) ∧ (∼p ∧ q) is a ______.


The logical statement [∼(q ∨ ∼r) ∨ (p ∧ r)] ∧ (q ∨ p) is equivalent to: ______ 


Which of the following is not a statement?


Negation of the Boolean expression `p Leftrightarrow (q \implies p)` is ______. 


∼ ((∼ p) ∧ q) is equal to ______.


Without using truth table prove that

[(p ∧ q ∧ ∼ p) ∨ (∼ p ∧ q ∧ r) ∨ (p ∧ q ∧ r) ∨ (p ∧ ∼ q ∧ r) ≡ (p ∨ q) ∧ r


Show that the simplified form of (p ∧ q ∧ ∼ r) ∨ (r ∧ p ∧ q) ∨ (∼ p ∨ q) is q ∨ ∼ p.


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×